2021
DOI: 10.3389/fonc.2021.751904
|View full text |Cite
|
Sign up to set email alerts
|

Herbal NF-κB Inhibitors Sensitize Rituximab-Resistant B Lymphoma Cells to Complement-Mediated Cytolysis

Abstract: BackgroundDrug resistance remains a serious challenge to rituximab therapy in B-NHL (B cell non-Hodgkin’s lymphoma). CDC (complement-dependent cytotoxicity) has been proposed as a major antitumor mechanism of rituximab, and direct abrogation of CD59 function partially restores rituximab sensitivity with high efficacy. However, universal blockade of CD59 may have deleterious effects on normal cells. Sp1 regulates constitutive CD59 expression, whereas NF-κB and CREB regulate inducible CD59 expression.MethodsImmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The study of Ge et al indicated that herbal products curcumin and perillyl alcohol could activate rituximab-mediated CDC in rituximab-resistant B lymphoma cell lines by the inhibition of CD59 expression. 97 In blood samples from lymphoma patients with less than 10% rituximab-mediated CDC, Golay J et al observed a 2-to 3-fold increase of lymphocytolysis by adding a single anti-CD55 or anti-CD59 blocking antibody and an up to 10-fold increase by adding both antibodies. 98 There are still limitations in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Ge et al indicated that herbal products curcumin and perillyl alcohol could activate rituximab-mediated CDC in rituximab-resistant B lymphoma cell lines by the inhibition of CD59 expression. 97 In blood samples from lymphoma patients with less than 10% rituximab-mediated CDC, Golay J et al observed a 2-to 3-fold increase of lymphocytolysis by adding a single anti-CD55 or anti-CD59 blocking antibody and an up to 10-fold increase by adding both antibodies. 98 There are still limitations in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al also demonstrated that in rituximab-resistant Raji 32 and LY8 cells, herbal products curcumin and perillyl alcohol can suppress the expression of only inducible CD59 but not CD20 and consequently sensitize those rituximab-resistant B lymphoma cells to CDC effect. 97 Besides, in a series of in vitro studies using blood samples from prolymphocytic leukemia (PLL) and B-cell chronic leukemia (B-CLL) patients, Golay J. and his colleagues also found that in the presence of antibodies blocking negative complement regulators and inhibitory proteins, the lymphocytolysis efficacy of rituximab could be significantly improved. 98 They reported a lymphocytolysis at 2- to 3-fold increase with adding a single blocking antibody and up to 10-fold increase with adding both anti-CD55 and anti-CD59 in samples from patients with low rituximab-mediated CDC (less than 10%); However, in high responders group (more than 50% rituximab-mediated CDC), lymphocytolysis was complete in the presence of single blocking antibodies.…”
Section: Manipulations Of Complement Cascade As Anti-cancer Strategiesmentioning
confidence: 99%
“…It is known that CD20 is a prerequisite for rituximab anti-tumor activity. Inhibiting the expression of CD59 is a good strategy for overcoming resistance [251]. Both curcumin and perillyl alcohol suppress activation of NF-κB and CREB, and subsequently restrain expression of CD59 but not CD20, thereby sensitizing rituximab-resistant B lymphoma cells [251].…”
Section: Lymphomasmentioning
confidence: 99%
“…Inhibiting the expression of CD59 is a good strategy for overcoming resistance [251]. Both curcumin and perillyl alcohol suppress activation of NF-κB and CREB, and subsequently restrain expression of CD59 but not CD20, thereby sensitizing rituximab-resistant B lymphoma cells [251]. In conclusion, curcumin may be a potential adjuvant drug to enhance the efficacy of chemotherapy drugs in leukemias and lymphomas but clinical application needs additional data support.…”
Section: Lymphomasmentioning
confidence: 99%
“…FunRich analysis demonstrated interactions among these proteins, with a focus on CREB1 (Figure -S12B). On the basis of published literature that implicated these four proteins in the regulation of the nuclear factor-κB (NF-κB) signaling pathway, [26][27][28][29] the protein-protein interaction (PPI) network and schematic diagram that contained key proteins (NEDD4, IKBKG, CACTIN, and OTUD7B) suggested that CREB1, DEAF1, and N4BP1 might negatively regulate NF-κB signaling (Figure S12C).…”
Section: Survival Analysis and Functional Enrichment For N4bp1 And Cr...mentioning
confidence: 99%